2019
DOI: 10.1371/journal.pone.0215318
|View full text |Cite
|
Sign up to set email alerts
|

Wanting without enjoying: The social value of sharing experiences

Abstract: Social connection can be a rich source of happiness. Humans routinely go out of their way to seek out social connection and avoid social isolation. What are the proximal forces that motivate people to share experiences with others? Here we used a novel experience-sharing and decision-making paradigm to understand the value of shared experiences. In seven experiments across Studies 1 and 2, participants demonstrated a strong motivation to engage in shared experiences. At the same time, participants did not repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 47 publications
(84 reference statements)
4
22
0
Order By: Relevance
“…Contrary to our hypothesis, however, participants did not report feeling more emotional during the joint condition compared to solo (F(1,51) = 0.005, p = 0.95). These null results do converge with recent work showing that shared video watching tasks do not meaningfully impact emotional ratings 55 .…”
Section: Affect and Togetherness Ratingssupporting
confidence: 89%
See 1 more Smart Citation
“…Contrary to our hypothesis, however, participants did not report feeling more emotional during the joint condition compared to solo (F(1,51) = 0.005, p = 0.95). These null results do converge with recent work showing that shared video watching tasks do not meaningfully impact emotional ratings 55 .…”
Section: Affect and Togetherness Ratingssupporting
confidence: 89%
“…Evidence suggests that positive emotions are linked to greater well-being 79 and that sharing positive experiences with others leads to greater resilience 80 , so there may be psychological benefits to the individual engaging in sharing behavior. Additionally, sharing experiences can lead to increased willingness to engage with a stranger and greater social bonding in both adults and children 3,55,[81][82] , so this may also serve as a way to form or strengthen social relationships among the pair.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have studied various aspects of meaningful social interactions for decades (Baumeister & Leary, 1995;Bhargave & Montgomery, 2013;Blumer, 1986;Hardin & Higgins, 1996;Jolly et al, 2019;Levine & Higgins, 2001;Searle & Willis, 1995). While an abundance of research Emotional impact Describes the interaction as leading to emotions such as empathy, sadness, authenticity, or love.…”
Section: Defining Meaningful Social Interactions and Understanding Thmentioning
confidence: 99%
“…Humans are one of the only species that engage in interactions for purely social purposes (Gelfand, 2018) and often opt for social experiences over solo ones "even in the absence of a hedonic boost, and at a monetary loss" (Jolly et al, 2019, p. 15). However, not all social interactions are equal; it is the deeper and more meaningful ones that people yearn for from infancy to old age (Baumeister & Leary, 1995;Bhargave & Montgomery, 2013;Blumer, 1986;Hardin & Higgins, 1996;Jolly et al, 2019;Levine & Higgins, 2001;Searle & Willis, 1995).…”
mentioning
confidence: 99%
“…Engaging in shared activities/experiences has been identified as one key aspect of relationship maintenance (Rossignac-Milon & Higgins, 2018), and human beings have an inherent motivation to seek out shared experiences with others (Jolly et al, 2019). For example, Girme et al (2014) found that couples engaging in more frequent shared activities reported greater perceived relationship quality both concurrently and longitudinally.…”
Section: The Potential Impact Of Covid-19 Lockdown On Social Relationmentioning
confidence: 99%